Hydrochemical Characteristics and Evolution Laws of Drinking Groundwater in Pengyang County, Ningxia, Northwest China. Issue 2 (2011) - Peiyue, Li; Hui, Qian; Jianhua, Wu
Abstract : The purpose of the paper is to identify the chemical characteristics of drinking groundwater and its distribution patterns in Pengyang County and to discover the hydrochemical evolution laws of groundwater. The temporal and spatial variation of groundwater hydrochemical characteristics and evolution laws were comprehensively and systematically studied based on the understanding of the geological, hydrogeological, meteorological and hydrological conditions. Many analytical methods such as descriptive statistics, geostatistical analysis, ionic ratio coefficient method and correlation analysis were adopted based on the underground water quality analysis data. Study results showed that variation coefficients of chemical parameters of pore water in unconsolidated rocks were relatively high which indicated that water chemical compositions are vulnerable to topography, meteorology, hydrology and human activities. TDS variation was in accordance with the changes in Ca 2+, Mg 2+ and SO 4 2- concentration. Hydrochemical type varied from HCO 3 SO 4 -Na Ca Mg type and HCO 3 SO 4 -Ca Mg type at the upper reaches towards gradually to HCO 3 -Na type at the lower reaches. Ionic ratio coefficient analysis showed that the hydrodynamic conditions of the pore water in loose rocks were better than that of pore-fissure water in clastic rocks and groundwater was non-marine deposited water. Its formation effects include the weathering leaching effects of the formation containing rock salt, water-rock interaction and cation exchange reaction. Hydrochemical characteristics were mainly controlled by geological and hydrogeological conditions. Correlation analysis showed that the dissolution of rock salt and sodium sulfate salt as well as calcite precipitation occurred in pore water and in pore-crack water in clastic rocks the dissolution of albite, K -feldspar and the precipitation of dolomite were also important effects.